Tingkat Pengetahuan Swamedikasi Pasien terhadap Obat Batuk di Apotek Sehati Bina Cakrawala Karawang - Fitri Dwi Wijayanti; Amalia Puspitasari (Detector: Jurnal Inovasi Riset Ilmu Kesehatan, 2025)
Self-medication is a common practice among the public in managing health complaints, including coughs. This study aims to assess the level of knowledge regarding self-medication for cough medicine among patients at Sehati Bina Cakrawala Pharmacy in Karawang during the June–July 2024 period. A descriptive research method was employed, with a sample of 132 respondents selected using purposive sampling. Data were collected through questionnaires and analyzed using univariate analysis with IBM SPSS 26 and Microsoft Excel. The findings indicate that out of 132 respondents, 93% had a good level of knowledge, 6% had a moderate level of knowledge, and 1% had a low level of knowledge regarding self-medication for cough medicine.